Comparison of APACHE II and three abbreviated APACHE II scores for predicting outcome among emergency trauma patients - Polita,Jorge Roberto (2014)
Objective: to compare the ability of the APACHE II score and three different abbreviated APACHE II scores: simplified APACHE II (s-APACHE II), Rapid Acute Physiology score (RAPS) and Rapid Emergency Medicine score to evaluate in-hospital mortality of trauma patients at the emergency department (ED). Methods: retrospective analysis of a prospective cohort study. All patients' victims of trauma admitted to the ED, during a 5 months period. For all entries to the ED, APACHE II score was calculated. APACHE II system was abbreviated by excluding the laboratory data to calculate s-APACHE II score for each patient. Individual data were reanalyzed to calculate RAPS and REMS. APACHE II score and its subcomponents were collected, and in-hospital mortality was assessed. The area under the receiver operating characteristic (AUROC) curve was used to determine the predictive value of each score. Results: 163 patients were analyzed. In-hospital mortality rate was 10.4%. s-APACHE II, RAPS and REMS scores were correlated with APACHE II score (r2= 0.96, r2= 0.82, r2= 0.92; p < 0.0001). Scores had similar accuracy in predicting mortality ([AUROC 0.777 [95% CI 0.705 to 0.838] for APACHE II, AUROC 0.788 [95% CI 0.717 to 0.848] for s-APACHE II, AUROC 0.806 [95% CI 0.737 to 0.864] for RAPS, AUROC 0.761 [95% CI 0.688 to 0.824] for REMS. Conclusion: abbreviated APACHE II scores have similar ability to evaluate in-hospital mortality of emergency trauma patients in comparison to APACHE II score.